2021
DOI: 10.3390/ijerph18126350
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Prevalence of Mental Health, Psychological Distress and Psychotropic Medication Consumption in Spain: A Nationwide Population-Based Study

Abstract: Background: To assess gender differences in the prevalence of self-reported mental disorders, psychological distress and psychotropic drug consumption, and to identify sociodemographic and health-related variables associated with these conditions in the male and female population (aged ≥ 18 years). Methods: A cross-sectional study was carried on 22,141 subjects aged 18 and over, using data from the Spanish National Health Interview Survey 2017. Results: We found an overall prevalence of mental disorders, psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
(90 reference statements)
2
10
1
Order By: Relevance
“…Differences in the prevalence of psychological distress by gender are to be expected, as the higher prevalence of mental disorders in women is a consistent finding in epidemiological studies. 40,41 Greater vulnerability in women has also been reported among healthcare workers during the pandemic. [42][43][44] Various explanations for these differences have been proposed, including response bias (men would have greater difficulty recognising and communicating psychological distress), as well as biological, social, and demographic factors.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Differences in the prevalence of psychological distress by gender are to be expected, as the higher prevalence of mental disorders in women is a consistent finding in epidemiological studies. 40,41 Greater vulnerability in women has also been reported among healthcare workers during the pandemic. [42][43][44] Various explanations for these differences have been proposed, including response bias (men would have greater difficulty recognising and communicating psychological distress), as well as biological, social, and demographic factors.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Furthermore, sex is an important factor affecting health status ( Wells et al, 2017 ). Previous evidence has suggested that sex differences exist in psychological distress and multimorbidity ( Violan et al, 2014 ; Agur et al, 2016 ; Maestre-Miquel et al, 2021 ). Females in China have lower salaries and education levels, less social support, fewer social activities, and greater rates of widowhood than males, all of which can contribute to psychological symptoms ( Ma et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for these results, already reported in other studies, may be related to differences in emotional processing in addition to intrinsic biological traits [32]. Adolescence is a time of behavioral divergence between boys and girls, probably due to different hormonal developments, although it is difficult to base this difference on objective parameters [33].…”
Section: Discussionmentioning
confidence: 83%